Increased mortality and morbidity in patients with chronic hypoparathyroidism: A population‐based study. (20th November 2018) - Vadiveloo, Thenmalar; Donnan, Peter T.; Leese, Callum J.; Abraham, Kirstin J.; Leese, Graham P.
Summary: Objectives: A population‐based study was undertaken to determine the mortality and morbidity for people with hypoparathyroidism compared to the general population. Methods: In this study, patients identified with chronic hypoparathyroidism using data linkage from regional datasets were compared with five age‐ and gender‐matched controls from the general population. Data from biochemistry, hospital admissions, prescribing and the demographic dataset were linked. Outcomes for mortality and specified conditions were examined for all patients and subdivided into post‐surgical and non‐surgical cases of hypoparathyroidism. Results: All patients had an increased risk of epilepsy (HR 1.65 [95% CI 1.12‐2.44]) and cataracts (HR 2.10 [1.30‐3.39]) but no increased fracture risk. Only non‐surgical hypoparathyroid patients also had increased mortality (HR 2.11 [1.49‐2.98]), cardiovascular disease (HR 2.18 [1.41‐3.39]), cerebrovascular disease (HR 2.95 [1.46‐5.97]), infection (HR 1.87 [1.2‐2.92]) and mental illness (HR 1.59 [1.21‐2.11]). There was an increased risk of renal failure (HR 10.05 [95% CI 4.71‐21.43]) during the first 2000 days (5.5 years) of follow‐up. Renal failure and death were associated with increasing serum calcium concentrations. Conclusion: Patients with hypoparathyroidism have an increased risk of cataract and epilepsy. Non‐surgical hypoparathyroidism is associated with increased mortality and additional morbidities.